2012
DOI: 10.1242/jeb.073320
|View full text |Cite
|
Sign up to set email alerts
|

Pressure and particle motion detection thresholds in fish: a re-examination of salient auditory cues in teleosts

Abstract: SUMMARYThe auditory evoked potential technique has been used for the past 30years to evaluate the hearing ability of fish. The resulting audiograms are typically presented in terms of sound pressure (dB re. 1Pa) with the particle motion (dB re. 1ms -2 ) component largely ignored until recently. When audiograms have been presented in terms of particle acceleration, one of two approaches has been used for stimulus characterisation: measuring the pressure gradient between two hydrophones or using acceleromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 46 publications
2
59
0
Order By: Relevance
“…Young and Fechter (Young and Fechter, 1983) found PPI thresholds in rats to be similar to auditory brainstem-evoked potential (ABR) thresholds, while Walter and colleagues (Walter et al, 2012) found PPI thresholds were 10-15dB SPL more sensitive than ABR thresholds in Mongolian gerbils. Our findings indicate that larval zebrafish have significant auditory capacity below levels that cause startle responses and the hearing threshold levels determined using the PPI paradigm are similar to AEP thresholds previously characterized for another otophysan fish, the goldfish (Radford et al, 2012). These findings suggest that the auditory system of 5d.p.f.…”
Section: Discussionsupporting
confidence: 83%
“…Young and Fechter (Young and Fechter, 1983) found PPI thresholds in rats to be similar to auditory brainstem-evoked potential (ABR) thresholds, while Walter and colleagues (Walter et al, 2012) found PPI thresholds were 10-15dB SPL more sensitive than ABR thresholds in Mongolian gerbils. Our findings indicate that larval zebrafish have significant auditory capacity below levels that cause startle responses and the hearing threshold levels determined using the PPI paradigm are similar to AEP thresholds previously characterized for another otophysan fish, the goldfish (Radford et al, 2012). These findings suggest that the auditory system of 5d.p.f.…”
Section: Discussionsupporting
confidence: 83%
“…Rainbow trout showed no effect of hearing loss after being exposed to sounds up to 150 dB re 1 μPa, therefore the exposure level of motorboat sound (125 dB re 1 μPa) in the present study is significantly less and unlikely to have caused any significant hearing damage to the protected fish. Also, snapper do not have ancillary hearing structures to promote greater sensitivity and bandwidth (Higgs & Radford 2013), hence are most sensitive to the particle motion component of the sound field (Radford et al., 2012). Motorboat particle motion measured in the center of the BUV frame suggests that the intensity is also not sufficient to cause any damage to the hearing of the fish.…”
Section: Discussionmentioning
confidence: 99%
“…Before experiments, fish were lightly anaesthesised with 0.004moll -1 2-phenoxy-ethanol (Sigma-Aldrich, St Louis, MO, USA) to allow placement into the testing apparatus and were kept under light anaesthesia with a constant flow of 0.002moll -1 2-phenoxy-ethanol over the gills. Previous experiments showed that there was no effect of anaesthetic on fish hearing thresholds (Radford et al, 2012). All fish were tested twice, first as a normal AEP and second after removal to one of the three experimental treatments (see below) for 3h.…”
Section: Fish Handlingmentioning
confidence: 98%
“…While there is a recent trend of presenting these results in terms of pressure and particle acceleration/displacement (e.g. Casper and Mann, 2006;Horodysky et al, 2008;Wysocki et al, 2009;Belanger et al, 2010;Radford et al, 2012), these studies invariably discuss the results as performance measures of the ear, largely ignoring lateral line inputs. While this approach is certainly justifiable when recording from single neurons or nerve bundles of the VIII nerve, it is less justified in whole-brain recordings such as those seen with auditory evoked potentials (AEPs; also called auditory brainstem responses, ABRs).…”
Section: Introductionmentioning
confidence: 99%